2019
DOI: 10.1200/jco.19.00189
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor Outcomes for Patients With Non–Small-Cell Lung Cancer Receiving Baseline Corticosteroids for Palliative Versus Nonpalliative Indications

Abstract: PURPOSE Baseline use of corticosteroids is associated with poor outcomes in patients with non–small-cell lung cancer (NSCLC) treated with programmed cell death-1 axis inhibition. To approach the question of causation versus correlation for this association, we examined outcomes in patients treated with immunotherapy depending on whether corticosteroids were administered for cancer-related palliative reasons or cancer-unrelated indications. PATIENTS AND METHODS Clinical outcomes in patients with NSCLC treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
178
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(198 citation statements)
references
References 19 publications
16
178
2
2
Order By: Relevance
“…Conversely, the effect of steroids administered to mitigate AEs did not seem to negatively affect OS; this finding was similar in NSCLC and melanoma. Similar results were presented by Ricciuti et al, where steroids' detrimental effect appeared to be linked to the poor-prognosis subgroup of patients who received corticosteroids for palliative indications [22]. This may be associated with a larger number of patients with poor performance status or brain metastases where steroids are provided for cancer-related palliation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Conversely, the effect of steroids administered to mitigate AEs did not seem to negatively affect OS; this finding was similar in NSCLC and melanoma. Similar results were presented by Ricciuti et al, where steroids' detrimental effect appeared to be linked to the poor-prognosis subgroup of patients who received corticosteroids for palliative indications [22]. This may be associated with a larger number of patients with poor performance status or brain metastases where steroids are provided for cancer-related palliation.…”
Section: Discussionsupporting
confidence: 80%
“…In total, 346 potentially relevant citations were reviewed (Figure 1). Ultimately, 16 studies published from 2009 to 2019 that reported OS and/or PFS data were included in the final analysis [17,[19][20][21][22][27][28][29][30][31][32][33][34][35][36][37]. The total number of patients included was 4045 ranging from 45 to 1025 patients per study (median, 151).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These predictive factors for nivolumab response in patients with NSCLC, including PS, are consistent with those identified in previous reports. 3,10,[19][20][21][22][23][24] The factors associated with PFS in nivolumab-treated patients with NSCLC with good PS were similar to those identified in the entire cohort. Smoking has been reported to enhance tumor mutation burden; consistent with this finding, nivolumab is efficacious in smokers.…”
Section: Discussionmentioning
confidence: 63%
“…17 Using the lowest effective dose minimizes steroidrelated toxicity but also may result in less suppression of immunotherapy effects. Conflicting data exist regarding whether all patients who receive ≥10 mg prednisone daily (or equivalent) at the initiation of single-agent, programmed cell death-1 (PD-1) or programmed death ligand 1 (PD-L1) inhibitors have worse OS and progression-free survival (PFS) compared with patients who require <10 mg. [18][19][20] Further investigation is necessary to determine the effects of corticosteroid use and their timing on the efficacy of immune checkpoint inhibition (ICI) therapy either alone or in conjunction with chemotherapy. Importantly, some patients who required corticosteroids in the aforementioned studies did demonstrate a response to ICI, so patients should not be excluded from immunotherapy if they are receiving corticosteroids.…”
Section: Symptom Managementmentioning
confidence: 99%